Evolution of gametocyte sex ratios in malaria and related apicomplexan (protozoan) parasites. - West, SA; Reece, SE; Read, A (2001)
'Survival of the fittest' is usually interpreted to mean that natural selection favours genes that maximize their transmission to the next generation. Here, we discuss recent applications of this principle to the study of gametocyte sex ratios in malaria and other apicomplexan parasites. Sex ratios matter because they are an important determinant of fitness and transmission success -- and hence of disease epidemiology and evolution. Moreover, inbreeding rates can be estimated from gametocyte sex ratios. The sex ratio is also an excellent model trait for testing the validity of important components of what is being marketed as 'Darwinian medicine'.